Permanent pastures identification in Portugal using remote sensing and multi-level machine learning - Morais, Tiago G.; Domingos, Tiago; Falcão, João; Camacho, Manuel; Marques, Ana; Neves, Inês; Lopes, Hugo; Teixeira, Ricardo F. M. (Frontiers in Remote Sensing, 2024)
IntroductionThe Common Agricultural Policy (CAP) is a vital policy framework implemented by the European Union to regulate and support agricultural production within member states. The Land Parcel Identification System (LPIS) is a key component that provides reliable land identification for administrative control procedures. On-the-spot checks (OTSC) are carried out to verify compliance with CAP requirements, typically relying on visual interpretation or field visits. However, the CAP is embracing advanced technologies to enhance its efficiency.MethodsThis study focuses on using Sentinel-2 time series data and a two-level approach involving recurrent neural networks (RNN) and convolutional neural networks (CNN) to accurately identify permanent pastures.ResultsIn the first step, using RNN, the model achieved an accuracy of 68%, a precision of 36%, a recall of 97% and a F1-score of 52%, which indicates the model’s ability to identify all the true positive parcels (correctly identified permanent pasture parcels) and minimize the false negative parcels (non-identified permanent pasture parcels). This occurs due to the difficulty in distinguishing between permanent pastures and other similar land covers (such as temporary pastures and shrublands). In the second step, it was possible to distinguish the permanent pasture parcels from the others. The obtained results improved significantly from the first to the second step. Using CNN, an accuracy of 93%, a precision of 89%, and a recall of 98% were achieved for the “Permanent pasture” class. The F1-score was 94%, indicating a balanced measure of the model’s performance.DiscussionThe integration of advanced technologies in the CAP’s control mechanisms, as demonstrated, has the potential to automate the verification of farmers’ declarations and subsequent subsidy payments.